واقع ومعوقات استخدام القيمة العادلة في القياس المحاسبي: دراسة تحليلية مقارنة بين مجموعة من الدول النامية (الجزائر، مصر، السعودية، الأردن) - زعيم, باهية; دادن, عبد الغني (جامعة الوادي - University of Eloued, 2016)
يهدف هذه البحث إلى دراسة وتحليل واقع ومعوقات تبني القيمة العادلة في البيئة المحاسبية الجزائرية ومقارنتها بواقع تبني القيمة العادلة في البيئة المحاسبية لبعض الدول النامية (مصر، السعودية، الأردن) باعتبارها من بين الدول النامية السباقة في ذلك، وسنحاول تشخيص التحديات التي تواجهها كل دولة في استخدام هذا النموذج في القياس المحاسبي والاستفادة من هذه التجارب في البيئة المحلية لمواجهة التحديات، وقد توصل البحث إلى أنه بالرغم من تبني مفهوم القيمة العادلة ضمن التشريعات الجزائرية إلا أن البيئة المحاسبية مازالت غير ملائمة لاستخدام القيمة العادلة، وعند مقارنتها بكل من مصر والسعودية والأردن نجد أن هذه الدول تبنت المعايير الدولية منذ فترة طويلة وقد توصلت في السنوات الأخيرة إلى إصدار معايير محلية خاصة بالقيمة العادلة إلا أنها مازالت هي الأخرى غير مطبقة لهذا الأسلوب في القياس المحاسبي بالمستوى المطلوب، كما تواجهها العديد من التحديات التي تقف حائلا أمام التطبيق السليم للقيمة العادلة في الممارسات المحاسبية، لكن بدرجة متفاوتة عن الممارسات المحاسبية الجزائرية The purpose of this research is to study and analyse the reality and the obstacles toward the adoption of the fair value in Algerian accounting environment and compare them by their implementation in certain developing countries (Egypt, Saudi Arabia, Jordan) as being among the first developing countries in that. In this case, we will attempt to diagnose the challenges that they faced in applying this model and to benefit from their experiences with our local accounting environment, to encounter this challenges. As a result, our study finds that even with the adoption of the concept of fair value in our legislation, the Algerian accounting environment is still not suitable to use this concept, But when we compared the application of this method to the countries mentioned above, we find that they have adopted the international standards for a long time and as a result of their experience they has been reached in the last few years to create a local standards at this field, however it is still not implemented on the required level ,because of, it is facing by many other challenges that stand in the way of the proper application of the fair value in practice accounting, but by varying degrees for the Algerian accounting practices.
The reality and constraints of the use of fair value in accounting measurement A comparative analysis among developing countries (Algeria, Egypt, Saudi Arabia, Jordan)
مقال بمجلة الدراسات المالية والمحاسبية . مج 07 ع01. ديسمبر 2016 . جامعة الوادي
Keywords: المعايير المحاسبية الدولية، البيئة المحاسبية، القياس المحاسبي، الممارسات المحاسبية، القيمة العادلة، السوق المالي; International Accounting Standards, accounting environment, accounting measure, accounting practices fair value Financial market